Structural and functional cardiac adaptations to a 10‐week school‐based football intervention for 9–10‐year‐old children. (August 2014) - Krustrup, P.; Hansen, P. R.; Nielsen, C. M.; Larsen, M. N.; Randers, M. B.; Manniche, V.; Hansen, L.; Dvorak, J.; Bangsbo, J.
Abstract : The present study investigated the cardiac effects of a 10‐week football training intervention for school children aged 9–10 years using comprehensive transthoracic echocardiography as a part of a larger ongoing study. A total of 97 pupils from four school classes were cluster‐randomized into a control group that maintained their usual activities (CON; two classes, n  = 51, 21 boys and 30 girls) and a football training group that performed an additional 3 × 40 min of small‐sided football training per week (FT; two classes, n  = 46, 23 boys and 23 girls). No baseline differences were observed in age, body composition, or echocardiographic variables between FT and CON. After the 10‐week intervention, left ventricular posterior wall diameter was increased in FT compared with CON [0.4 ± 0.7 vs −0.1 ± 0.6 (± SD) mm; P  < 0.01] as was the interventricular septum thickness (0.2 ± 0.7 vs −0.2 ± 0.8 mm; P  < 0.001). Global isovolumetric relaxation time increased more in FT than in CON (3.8 ± 10.4 vs −0.9 ± 6.6 ms, P  < 0.05) while the change in ventricular systolic ejection fraction tended to be higher (1.4 ± 8.0 vs −1.1 ± 5.5%; P  = 0.08). No changes were observed in resting heart rate or blood pressure. In conclusion, a short‐term, school‐based intervention comprising small‐sided football sessions resulted in significant structural and functional cardiac adaptations in pre‐adolescent children.